REQUIREMENTS FOR MOTHER TONGUE AND READING LITERACY CLASSES IN ELEMENTARY SCHOOL AND DEVELOPMENT OF INNOVATIVE PEDAGOGICAL TECHNOLOGIES - Gulsevar Abdurasul qizi Qurbonova; Usmanova Mokhira Kenjayevna (American Journals Publishing, 2025)
This article analyzes the key requirements for primary school native language and literacy lessons and the development of innovative pedagogical technologies. It emphasizes the necessity of applying modern methods and approaches, taking into account students' individual characteristics to improve the effectiveness of the educational process.
Keywords: Primary school, native language, literacy, educational requirements, innovative pedagogical technologies, interactive methods, individual approach.